Albert Watkins and Howard Watkins Family Genealogy Trip to Tennessee - Watkins, Howard::::::::: (1986)
Drugstore where school superintendent and others decided that it would bring much business to Dayton if John Scopes agreed to be tried for violating the Butler Act